2008
DOI: 10.1002/bit.22073
|View full text |Cite
|
Sign up to set email alerts
|

Biomining with bacteriophage: Selectivity of displayed peptides for naturally occurring sphalerite and chalcopyrite

Abstract: During mineral processing, concentrates of sulfide minerals of economic interest are formed by froth flotation of fine ore particles. The method works well but recovery and selectivity can be poor for ores with complex mineralogy. There is considerable interest in methods that improve the selectivity of this process while avoiding the high costs of using flotation chemicals. Here we show the first application of phage biotechnology to the processing of economically important minerals in ore slurries. A random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Other metal-binding phages are being considered for use as biofilms to decrease corrosion of metals [17]. In a novel application, we recently reported the use of filamentous phage in the recognition of naturallyoccurring minerals for potential use in a biomining setting [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other metal-binding phages are being considered for use as biofilms to decrease corrosion of metals [17]. In a novel application, we recently reported the use of filamentous phage in the recognition of naturallyoccurring minerals for potential use in a biomining setting [21].…”
Section: Introductionmentioning
confidence: 99%
“…This knowledge is being applied to the improvement of medical implants [12]. The list of metals to which phage-displayed peptides bind continues to grow [12][13][14][15][16][17][18][19][20][21]. Some of these semiconductor binding phages are being utilized in novel nanotechnology applications; for example, phages are being engineered to assist in the synthesis of nanowires [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The phage clone used in this study displays the sequence DSQKTNPS (VP12) and was shown to be highly selective for CuFeS 2 (Dunbar et al, 2008). Bacteriophage were produced and purified as described by Curtis et al (2009). Briefly, a single infected bacterial colony is grown up in NZY, the bacteria removed by centrifugation, and the phage purified by two sequential PEG/NaCl precipitations.…”
Section: Methodsmentioning
confidence: 99%
“…Using the technique of phage display and biopanning, we recently isolated phage that bind specifically to CuFeS 2 and sphalerite (ZnS; Curtis et al, 2009;Dunbar et al, 2008) and showed that large numbers of mineralbinding phage could be prepared by using computercontrolled fermentation (Grieco et al, 2009). The exact nature of the mineral-peptide interaction is unknown at present but not surprisingly, the mineral-binding peptide sequences contain primarily polar amino acids, both charged and uncharged.…”
Section: Introductionmentioning
confidence: 97%
“…Filamentous phages may also make their bacterial hosts less virulent or lower our dependency on pesticides to control pathogens, thereby contributing to sustainable restoration (Ahmad et al, 2014;Askora, Kawasaki, Fujie, & Yamada, 2012). Modified filamentous phages may also produce specific peptides or proteins that are useful in monitoring targeted toxins, toxicants, and pesticides in the environment and in holding soil particles together to reduce soil erosion (Curtis, Dunbar, & Macgillivray, 2013;Curtis, Hewitt, & Macgillivray, 2009;Curtis, Macgillivray, & Dunbar, 2011;Goldman et al, 2003;Goldman, Pazirandeh, Charles, Balighian, & Anderson, 2002). In fact, filamentous phages can bridge the gap between the efficacy of microbial activity in vitro and in the field.…”
Section: P Otential Are a S For The Appli C Ati On Of Fil Amentous mentioning
confidence: 99%